Efficient deformable shape correspondence via kernel matching - Vestner, Matthias; Laehner, Zorah; Boyarski, Amit; Litany, Or; Slossberg, Ron; Remez, Tal; Rodola, Emanuele; Bronstein, Alex; Bronstein, Michael; Kimmel, Ron; Cremers, Daniel (Proceedings - 2017 International Conference on 3D Vision, 3DV 2017, 2018)
We present a method to match three dimensional shapes under non-isometric deformations, topology changes and partiality. We formulate the problem as matching between a set of pair-wise and point-wise descriptors, imposing a continuity prior on the mapping, and propose a projected descent optimization procedure inspired by difference of convex functions (DC) programming.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Non-Rigid-Shapes; Shape-Correspondence